2004
DOI: 10.1046/j.1471-4159.2003.02270.x
|View full text |Cite
|
Sign up to set email alerts
|

Nonylphenol induces the death of neural stem cells due to activation of the caspase cascade and regulation of the cell cycle

Abstract: Endocrine disruptors (EDs) are a great concern throughout the world, because they have adverse effects on human health and wildlife. In the present study, we investigated the effects of EDs on the proliferation and survival of murine neural stem cells (NSCs). In contrast to bisphenol A, phthalic acid benzyl n-butyl ester, phthalic acid di-n-butyl ester and phthalic acid di(2-ethylhexyl) ester, the treatment of NSCs with 4-nonylphenol for 24 h inhibited cell growth in a concentration-dependent manner. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
41
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 28 publications
6
41
0
Order By: Relevance
“…A body of evidence from mainly in vitro studies, however, has demonstrated the estrogenicity (Soto et al, 1991 ;Vivacqua et al, 2003 ;White et al, 1994 ), cell proliferative-inducing (Masuno et al, 2003 ;Miura et al, 2005 ;Soto et al, 1991 ) and caspase-dependent death-inducing (Kudo et al, 2004 ;Yao et al, 2006 ) effects of weak estrogenic chemicals such as alkylphenolic compounds (e.g., nonylphenol and octylphenol). Nonylphenol production, which in the United States was 147 million pounds in 1980 and grew to over 230 million pounds in 2000 (Blankenship and Coady, 2005 ), are for diverse uses, ranging from industrial detergents and wetting agents to pesticides, hair dyes, and intravaginal spermicides (Bolt et al, 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“…A body of evidence from mainly in vitro studies, however, has demonstrated the estrogenicity (Soto et al, 1991 ;Vivacqua et al, 2003 ;White et al, 1994 ), cell proliferative-inducing (Masuno et al, 2003 ;Miura et al, 2005 ;Soto et al, 1991 ) and caspase-dependent death-inducing (Kudo et al, 2004 ;Yao et al, 2006 ) effects of weak estrogenic chemicals such as alkylphenolic compounds (e.g., nonylphenol and octylphenol). Nonylphenol production, which in the United States was 147 million pounds in 1980 and grew to over 230 million pounds in 2000 (Blankenship and Coady, 2005 ), are for diverse uses, ranging from industrial detergents and wetting agents to pesticides, hair dyes, and intravaginal spermicides (Bolt et al, 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“…This study suggested that modulation of NSC 'stemness', growth, and differentiation was EDC dependent. Furthermore, NSCs in the early stages of differentiation were more sensitive to endocrine disruption than undifferentiated neurospheres or differentiated neurons (Kudo et al 2004).…”
Section: Disruption Of Neural Developmentmentioning
confidence: 98%
“…The EDC 4-NP also regulated neural stem cell (NSC) survival and proliferation (Kudo et al 2004). 4-NP exposure inhibited murine NSC proliferation in a dosedependent manner by inducing G2/M phase arrest, downregulating cyclin A and B1 expression and promoting apoptosis.…”
Section: Disruption Of Neural Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also caused by pathological or environmental factors such as certain viruses, bacteria, radiations, natural compounds, and chemicals. Various EDCs have been reported to induce apoptosis in various types of cells, [2][3][4][5][6][7][8][9][10][11][12][13][14] suggesting that those chemicals exert cell toxicity by triggering the apoptotic signals. However, another possibility that EDCs may enhance or suppress the apoptotic signals induced by physiological or other factors has not been investigated.…”
Section: Introductionmentioning
confidence: 99%